2010
DOI: 10.1053/j.gastro.2009.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of IκB-Kinase-β Accelerates Helicobacter-Dependent Gastric Apoptosis, Proliferation, and Preneoplasia

Abstract: BACKGROUND & AIMS-The NF-κB/IKKβ pathway has been shown to represent a key link between inflammation and cancer, inducing pro-inflammatory cytokines in myeloid cells and antiapoptotic pathways in epithelial cells. However, the role of NF-κB pathway in gastric carcinogenesis and injury has not been well defined. We derived mice with a conditional knockout of Ikkβ in gastric epithelial cells (GECs) and myeloid cells, and examined responses to ionizing radiation (IR) and Helicobacter felis (Hf) infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…Moreover, it has been demonstrated that the IKKbinduced NF-kB activation in myeloid cells is important for inflammatory responses and proliferation in the stomach after Helicobacter infection (38). Taken together, these results indicate that the TLR/MyD88/NF-kB signaling in BMDCs plays a key role in generating the inflammatory microenvironment in tumor tissues.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, it has been demonstrated that the IKKbinduced NF-kB activation in myeloid cells is important for inflammatory responses and proliferation in the stomach after Helicobacter infection (38). Taken together, these results indicate that the TLR/MyD88/NF-kB signaling in BMDCs plays a key role in generating the inflammatory microenvironment in tumor tissues.…”
Section: Discussionsupporting
confidence: 59%
“…We found elevated apoptosis in infected Myd88 Ϫ/Ϫ mice in comparison to infected WT mice, suggesting involvement of MyD88 signaling in the regulation of apoptosis during infection with Helicobacter. Increased apoptosis in Myd88 Ϫ/Ϫ mice was followed by increased cell proliferation, which was similar to that reported in mice with a deletion in IKK␤ (23). The hyperproliferation we observed in Myd88 Ϫ/Ϫ mice was most likely in response to the high apoptotic rate in these mice, which is thought to be compensatory proliferation that is implicated in promoting carcinogenesis (30,31).…”
Section: Fig 4 Infection Of Myd88supporting
confidence: 72%
“…S2 in the supplemental material). Shibata et al (23) reported similar inflammation scores between WT mice and mice with a deletion in IKK␤, which is downstream of MyD88 signaling, in response to infection with H. felis. Together, these studies indicate that infiltration of immune cells into the mucosa and submucosa may not be the main factor responsible for the rapid development of premalignant and malignant lesions we observed in Myd88 Ϫ/Ϫ mice during infection.…”
Section: Myd88mentioning
confidence: 83%
See 1 more Smart Citation
“…Several reports suggested that inflammatory responses initiated by IL-1 play a pivotal role, and others showed that antiapoptotic pathways governed by IL-1 signaling were responsible for carcinogenic potential (51)(52)(53). Human single nucleotide polymorphism data also indicated the importance of IL-1␤ in the progression of gastric atrophy (5,54).…”
Section: Discussionmentioning
confidence: 96%